PEMBELAJARAN KOLABORATIF BERBASIS PROYEK PADA PEMBUATAN MURAL DI TB-TK SANTA URSULA BANDUNG - Aryani, Dewi Isma; Pandanwangi, Ariesa; Wangsaputra, Priscylia Susanto; Baene, Basituasi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2024)
Maranatha Christian University is a private university in Bandung which claims to be a research- based teaching university by upholding the ICE values, namely integrity, care, excellence in its tridharma program. One of them is in the form of community service activities through the art medium of wall painting (murals) involving lecturers from the Bachelor of Visual Communication Design Program and the Bachelor of Fine Arts Program, Faculty of Fine Arts and Design as material formulators and facilitators. The activity entitled